The Optimization of the Caucus Roles in the Mediation for Dispute Resolution at Mataram Religious Court and Praya Religious Court - Ahmad Mustarudin Efendi, Subhan Abdullah Acim, Jumarim, Syukri (Journal of Educational Studies, 2025)
This study examines the optimization of caucus roles in mediation for dispute resolution at the Religious Courts of Mataram and Praya, Indonesia. Despite the mandatory implementation of mediation under Supreme Court Regulation (PERMA) No. 1 of 2016, mediation success rates in Religious Courts remain relatively low, indicating a gap between normative expectations and practical outcomes. This research aims to analyze the implementation of caucus, identify factors influencing its effectiveness, and formulate a model for optimizing mediation practices. Employing an empirical legal research design with a qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving mediators, judges, court administrators, and disputing parties. The findings reveal that caucus serves as a strategic mediation instrument for overcoming communication barriers, reducing emotional tensions, exploring hidden interests, and facilitating constructive negotiations. Mediation effectiveness is influenced by legal substance, institutional structure, legal culture, mediator competence, interpersonal communication, psychological characteristics of disputing parties, and the strategic utilization of caucus. Among these factors, mediator competence emerged as the most influential determinant. This study further develops the Integrated Mediator-Based Effectiveness Theory, which positions the mediator as the central actor responsible for integrating legal, communicative, psychological, and Maq??id al-Shar?‘ah dimensions within the mediation process. The study contributes both theoretically and practically to strengthening mediation effectiveness, promoting substantive justice, and fostering sustainable social harmony within Religious Courts.